2018
DOI: 10.1007/s11126-018-9585-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Clerkship Knowledge, Perceptions, and Acceptability of Electroconvulsive Therapy (ECT) in 3rd Year Medical Students

Abstract: To examine the impact of the third year psychiatry clerkship on medical students' knowledge and opinion of ECT at University of Missouri-Columbia School of Medicine. Despite overwhelming evidence of ECT's efficacy and safety for refractory affective illnesses, (among other conditions), it remains a misunderstood and underutilized intervention. Several studies indicate that ECT stigma and misinformation, unfortunately, does not spare the medical community. Medical students are an optimal group to study, as they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Despite the knowledge that electroconvulsive therapy (ECT) is highly effective in the treatment of major depressive episodes (1) and that ECT is safe and well tolerated, it is still plagued by stigma and negative perceptions (2)(3)(4). A significant proportion of patients experience anxiety for ECT (5,6), often to such an extent that it negatively impacts treatment compliance (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the knowledge that electroconvulsive therapy (ECT) is highly effective in the treatment of major depressive episodes (1) and that ECT is safe and well tolerated, it is still plagued by stigma and negative perceptions (2)(3)(4). A significant proportion of patients experience anxiety for ECT (5,6), often to such an extent that it negatively impacts treatment compliance (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…31% of third-year medical students believed, in one study, that ECT was used as punishment, and 32% of third-year medical students believed that ECT could cause brain damage in another. 2 Within the same study, 50% believed the procedure to be dangerous. 2 Several studies have indicated many patients and nurses involved with ECT are simply not well educated on the treatment, with most of the knowledge being obtained from sources within popular culture, such as cinema.…”
Section: Significancementioning
confidence: 94%
“…2 Within the same study, 50% believed the procedure to be dangerous. 2 Several studies have indicated many patients and nurses involved with ECT are simply not well educated on the treatment, with most of the knowledge being obtained from sources within popular culture, such as cinema. 5,6,7 The lack of education for psychiatric nursing contributes to negative beliefs about ECT, which creates difficulty in assigning nurses to ECT within a hospital setting.…”
Section: Significancementioning
confidence: 94%
See 1 more Smart Citation
“…Stigma, lack of knowledge about modern techniques, and inappropriate teaching have all been proposed as key factors to explain the underutilization of ECT. Particularly, several studies found that nurses, medical students, or physicians frequently have negative opinions about ECT and its adverse effects, sometimes describing the technique as a cruel treatment 2 …”
mentioning
confidence: 99%